Development of competencies of pediatric residents and teachers in screening and surveillance of preschool children - Caguioa, Maria Cristina R.; Erlyn A. Sana, PhD (Manila National Teacher Training Center for the Health Professions, 2019)
A gap is seen in the implementation of screening and surveillance of children in the out-patient setting and in the community. Pediatric residents and teachers should undergo a training workshop to transfer appropriate knowledge and skills to strengthen screening and surveillance in their workplace. The objectives of the study are to (1) determine the effect of training on the competencies of residents and teachers in screening and surveillance of preschool children and (2) determine the acceptability and usefulness of doing screening and surveillance using the Filipino-translated 60-month ages and stages questionnaire (ASQ).

This study employed a static group pre-test and post-test design using two independent groups. Four pediatric third year residents from a public tertiary hospital rotating in the community and fourteen public school teachers in Manila were included. This study assessed the knowledge, psychomotor skills, and attitudes of residents and teachers before and after training them on surveillance and screening of developmental delays in preschool children. They were given multiple choice question examination pre and post training. Descriptive statistics, inferential statistics, and thematic content analysis were used to determine effects on skills and attitudes as well as the acceptability of the ASQ. T- test for unmatched pairs was used to determine the effect of the training on the knowledge domain.

There was a significant difference between the pre and post-test scores of the
respondents with a t-value of 3.66 for residents at p=0.035 and 4.42 for teachers at p=0.001. For the psychomotor skill using the checklist, both respondents mostly performed the skills correctly. The collected ASQ forms shows that both respondents are highly competent in administering the ASQ. Overall, both residents and teachers are competent in terms of knowledge, psychomotor and affective domains. Thematic content analysis revealed that respondents found the Filipino-translated ASQ as acceptable in terms of ease of use, time allotted, and problems encountered. It is useful in terms of its value on the respondent’s professional role. The results of this study emphasize the vital role of these professionals in Universal Health Care that encourages collaboration or team work out of the regular hospital and school settings in order to build the health and well-being of children.
Thesis (Master in Health Professions Education)
Panel members: Erlyn A. Sana, PhD, chair/adviser; Joshua A. Marcos, MD, MSc, MPH, reader/critic. Members: Melflor A. Atienza, MD, MHPEd; Elynn L. Go, MD, MHPEd; Merle P. Tan, MD, MHPEd.
Keywords: Pediatrics -- Study and teaching (Residency); Pediatricians